Electrochemical, Spectrophotometric and Liquid-Chromatographic Approaches for Analysis of Tropical Disease Drugs - Santos, Andre L.; Takeuchi, Regina M. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Bentham Science Publ Ltd, 2009)
Drug analysis is important in several phases of drug development, such as formulation, stability studies and quality control. The importance of reliable analytical methods for drug determination in a fast, inexpensive, sensitive and selective way is thus evident. Although there are countless works describing new analytical methods for determination of drugs that act against tropical diseases, a review organizing these works in a systematic and complete way is lacking. In this context, the objective of this review is to present the main advances in the development of analytical methods for determination of tropical disease drugs using electroanalytical, spectrophotometric and liquid chromatographic techniques.
Keywords: Tropical diseases; Analytical methods; Drug analysis; Electroanalytical; Spectrophotometry; Chromatography